KCa3.1/IK1 Channel Regulation by cGMP-Dependent Protein Kinase (PKG) via Reactive Oxygen Species and CaMKII in Microglia: An Immune Modulating Feedback System? - Ferreira, Roger; Wong, Raymond; Schlichter, Lyanne C. (Frontiers in Immunology, 2015)
The intermediate conductance Ca2+-activated K+ channel, KCa3.1 (IK1/SK4/KCNN4) is widely expressed in the innate and adaptive immune system. KCa3.1 contributes to proliferation of activated T lymphocytes, and in CNS-resident microglia, it contributes to Ca2+ signaling, migration, and production of pro-inflammatory mediators (e.g., reactive oxygen species, ROS). KCa3.1 is under investigation as a therapeutic target for CNS disorders that involve microglial activation and T cells. However, KCa3.1 is post-translationally regulated, and this will determine when and how much it can contribute to cell functions. We previously found that KCa3.1 trafficking and gating require calmodulin (CaM) binding, and this is inhibited by cAMP kinase (PKA) acting at a single phosphorylation site. The same site is potentially phosphorylated by cGMP kinase (PKG), and in some cells, PKG can increase Ca2+, CaM activation, and ROS. Here, we addressed KCa3.1 regulation through PKG-dependent pathways in primary rat microglia and the MLS-9 microglia cell line, using perforated-patch recordings to preserve intracellular signaling. Elevating cGMP increased both the KCa3.1 current and intracellular ROS production, and both were prevented by the selective PKG inhibitor, KT5823. The cGMP/PKG-evoked increase in KCa3.1 current in intact MLS-9 microglia was mediated by ROS, mimicked by applying hydrogen peroxide (H2O2), inhibited by a ROS scavenger (MGP), and prevented by a selective CaMKII inhibitor (mAIP). Similar results were seen in alternative-activated primary rat microglia; their KCa3.1 current required PKG, ROS, and CaMKII, and they had increased ROS production that required KCa3.1 activity. The increase in current apparently did not result from direct effects on the channel open probability (Po) or Ca2+ dependence because, in inside-out patches from transfected HEK293 cells, single-channel activity was not affected by cGMP, PKG, H2O2 at normal or elevated intracellular Ca2+. The regulation pathway we have identified in intact microglia and MLS-9 cells is expected to have broad implications because KCa3.1 plays important roles in numerous cells and tissues.